Marriage as Insurance: Job Protection and Job Insecurity in France - Andrew E. Clark; Conchita D'Ambrosio; Anthony Lepinteur (Institute of Labor Economics (IZA), 2022)
Job insecurity is one of the risks that workers face on the labour market. As with any risk, individuals can choose to insure against it, and we here consider marriage as one potential source of this insurance. The 1999 rise in the French Delalande tax, paid by larger private firms when they laid off workers aged 50 or over, led to an exogenous rise in job insecurity for the uncovered (younger workers) in these larger firms. A difference-in-differences analysis using French panel data reveals that this greater job insecurity for the under-50s led to a significant rise in their probability of marriage, and especially when the partner had greater job security, consistent with marriage providing insurance against labour-market risk.
Keywords: I38; J13; J18; 330; employment protection; insurance; marriage; difference-in-differences